The Transmission Electron Microscope - Theory and Applications 2015
DOI: 10.5772/60673
|View full text |Cite
|
Sign up to set email alerts
|

Transmission Electron Microscopy of Platelets FROM Apheresis and Buffy-Coat-Derived Platelet Concentrates

Abstract: Platelet concentrates are produced in order to treat bleeding disorders. They can be provided by apheresis machines or by pooling of buffy coats from four blood donations. During their manufacturing and storage, morphological alterations of platelets occur which can be demonstrated by transmission electron microscopy. Alterations range from slight and reversible changes, such as formation of small cell protrusions and swelling of the surface-connected open canalicular system, to severe structural changes, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 120 publications
1
28
0
3
Order By: Relevance
“…The interaction of platelets (PLTs) with bacteria has been shown in PLT concentrates after spiking with Staphylococcus aureus . The uptake of these bacteria into the open canalicular system (OCS) was visualized by using ET [ 49 , 50 ]. Bacterial contamination leads to activation of PLTs and to the formation of platelet microparticles (PMPs; Fig.…”
Section: Et Investigations Carried Out In Our Departmentmentioning
confidence: 99%
“…The interaction of platelets (PLTs) with bacteria has been shown in PLT concentrates after spiking with Staphylococcus aureus . The uptake of these bacteria into the open canalicular system (OCS) was visualized by using ET [ 49 , 50 ]. Bacterial contamination leads to activation of PLTs and to the formation of platelet microparticles (PMPs; Fig.…”
Section: Et Investigations Carried Out In Our Departmentmentioning
confidence: 99%
“…Mitochondria and glycogen provide the energy required for secretory functions. Upon activation, platelets change their shape dramatically, acquiring an amoeboid form due to the rearrangement of organelles, and secrete various bioactive components involved in haemostasis, regeneration, repair, and inflammation …”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated that people of different age groups show different platelet and fibrin morphologies . Furthermore, several studies have demonstrated that transmission electron microscopy (TEM) is an appropriate tool for evaluating platelet quality . TEM can be used to clearly identify a large number of platelet structural elements, including the open canalicular system (OCS), the dense tubular system (DTS), and various organelles, such as α‐granules, dense granules, lysosomal granules, and mitochondria.…”
Section: Introductionmentioning
confidence: 99%
“…Based on published observations, the size of the cytoplasm was reduced as the observed volume of platelets is filled by organelles such as vesicles, ER remnant, mitochondria and the OCS estimated to occupy up to 40% of the internal volume. Most of the remaining volume contains cytoskeletal proteins and glycogen granules and is calculated to occupy around 1 to 2 fl 37,41,42 . We estimated the mouse platelet plasma membrane and cytosol volumes to be around 0.25 fl each while the nucleated cells average plasma membrane and reaction cytosol volumes at around 17 fl each based on a 2000 fl overall cell volume.…”
Section: Methodsmentioning
confidence: 99%